The Effect of Soil on the Biochemical Plasticity of Berry Skin in Two Italian Grapevine (V. vinifera L.) Cultivars - Perin, Corrado; Fait, Aaron; Palumbo, Fabio; Lucchin, Margherita; Vannozzi, Alessandro (Frontiers in Plant Science, 2020)
Grapevine represents a particularly interesting species for what concerns phenotypic plasticity, considering that the terroir, meant as the contribution of geography, geology and climate of a certain place, together with the agronomical practices utilized, may deeply influence the berry phenotype at the physiological, molecular, and biochemical level. This phenomenon leads to the production of wines that, although produced from the same variety, exhibit different enological profiles and represent an issue of increasing interest from both a biological and economical point of view. The main objective of the present study was to deepen the determinism of phenotypic plasticity in grapevine, trying to dissect the role of one its important components – the soil – investigating on the singular effect that different physico-chemical soil properties can produce in terms of berry plasticity at phenological, physiological and biochemical level in both a red and a white variety of great economic importance in Italy and overseas: Corvina and Glera. Results indicated a genotype-dependent response to soil factor with a higher biochemical plasticity in Corvina respect to Glera and suggested a key role of specific soil properties including skeleton, texture and mineral composition on the metabolite profile of berry skin.